Strength Analysis of 120 Tons Maximum Payload Using Finite Element Method - MARULI (NIM 13104105), MICHAEL
Transportation is one of the most important sectors to support the industry and truck is the most common vehicle used in industry. PT United Tractors Pandu Engineering, one of the truck and heavy equipment producer, has a 120 tons payload capacity low-bed trailer design that is need to be analyzed by finite element method. In this research, loading analysis and stress analysis carried out on lowbed trailer structure under several operating condition. Low-bed trailer structure 3D modeled by Autodesk Inventor software and analyzed using ANSYS 11 software. Load cases that modeled are:(1) Static loading (2) truck accelerating, (3) truck retarding, (4) truck turning, and (5) Wong J. Y. loading criteria. The analysis affords the performance and safety factor of existing low-bed trailer structure. The results of analysis become a reference in modifying to obtain good performance and optimum weight of low-bed trailer structure. The analysis results show that the existing low-bed trailer structure is not safety, with the lowest safety factor is 0,2. Trailer's part that fails is horizontal neck support beam. Modification has been made to reduce the possibility of these failures. The safest modification has been done by changing the material to Hardox 400 and SM490YA. By this modification, the lowest safety factor is could be increased to 1,04.